Facilitating critical thinking in decision making-based professional training: An online interactive peer-review approach in a flipped learning context. (November 2021) - Lin, Hui-Chen; Hwang, Gwo-Jen; Chang, Shao-Chen; Hsu, Yaw-Don
Abstract: Designing activities for learners to deal with problems and cultivate their higher order thinking is critical in professional training. Peer review is to allow a group of learners with similar abilities and knowledge background to promote their higher order thinking and reflective thinking through mutual observation and comments. However, in the conventional peer-review approach, the interaction between assessors and assessees is one-way. That is, assessors cannot receive any responses from assessees, so they have no opportunity to reflect on their comments. The online interactive peer-review approach aims to enable assessees to express their points of view and to allow assessors to understand whether their ratings and comments are accurate or helpful to assessees. During the interaction, both assessors and assessees have the opportunity for reflection, which then promotes the quality of ratings and comments and facilitates their learning effectiveness and critical thinking. The present study developed an online interactive peer-review system and applied it to the health assessment learning course for nurse practitioners (NP). An experiment was designed to explore the effects of different online peer-review approaches on NP students' learning achievement and higher order thinking. Also, the study recorded the students' peer-review content and analyzed its effects on the quality of their peer review. The experimental group adopted the online interactive peer-review approach, while the control group adopted the conventional online peer-review approach in a flipped learning context. The results indicated that integrating the online interactive peer-review learning approach could not only strengthen the NP students' knowledge and clinical skills, but could also significantly improve their critical thinking tendency and reflective thinking. Moreover, based on the analytic findings of the peer-review content, students using the online interactive peer-review approach were better able to significantly address more specific suggestions to assist their peers in improving their health assessment performance than those using the conventional online peer-review approach. Highlights: An online interactive peer-review approach was proposed. The approach aimed to promote students' performance in decision-making tasks. An experiment was conducted in a health assessment skills training course. The approach improved the performance of students' health assessment skills. The approach improved the students' reflection and peer-assessment quality.